Licence to swill: James Bond's drinking over six decades - Wilson, N; Tucker, A; Heath, D; Scarborough, P (Wiley, 2018)
Objectives: To describe the patterns of alcohol use in James Bond movies over six decades. Design: Film content analysis. Setting: Wide range of international locations in 24 James Bond movies (Eon Productions series, 1962–2015). Main outcome measures: Drinking episodes for Bond and major female characters; alcohol product placement in films; peak estimated blood alcohol concentrations; features relevant to DSM‐5 criteria for alcohol use disorder. Results: Bond has drunk heavily and consistently across six decades (109 drinking events; mean, 4.5 events per movie). His peak blood alcohol level was estimated to have been 0.36 g/dL, sufficient to kill some people. We classified him as having severe alcohol use disorder, as he satisfied six of 11 DSM‐5 criteria for this condition. Chronic risks for Bond include frequently drinking prior to fights, driving vehicles (including in chases), high stakes gambling, operating complex machinery or devices, contact with dangerous animals, extreme athletic performance, and sex with enemies, sometimes with guns or knives in the bed. Notable trends during the study period included a decline in using alcohol as a weapon (P = 0.023) and an increase in the number of alcohol products in his environment (for alcohol‐related product placement: P < 0.001), but his martini consumption has been steady. Drinking by lead female characters and a random selection of 30 of his sexual partners was fairly stable over time, but also occasionally involved binges. Conclusions: James Bond has a severe chronic alcohol problem. He should consider seeking professional help and find other strategies for managing on‐the‐job stress.